A fungal anticodon nuclease ribotoxin exploits a secondary cleavage site to evade tRNA repair - Meineke, Birthe; Kast, Alene; Schwer, Beate; Meinhardt, Friedhelm; Shuman, Stewart; Klassen, Roland (RNA (Cambridge), 2012)
PaOrf2 and γ-toxin subunits of Pichia acaciae toxin (PaT) and Kluyveromyces lactis zymocin are tRNA anticodon nucleases. These secreted ribotoxins are assimilated by Saccharomyces cerevisiae, wherein they arrest growth by depleting specific tRNAs. Toxicity can be recapitulated by induced intracellular expression of PaOrf2 or γ-toxin in S. cerevisiae . Mutational analysis of γ-toxin has identified amino acids required for ribotoxicity in vivo and RNA transesterification in vitro. Here, we report that PaOrf2 residues Glu9 and His287 (putative counterparts of γ-toxin Glu9 and His209) are essential for toxicity. Our results suggest a similar basis for RNA transesterification by PaOrf2 and γ-toxin, despite their dissimilar primary structures and distinctive tRNA target specificities. PaOrf2 makes two sequential incisions in tRNA, the first of which occurs 3′ from the mcm 5 s 2 U wobble nucleoside and depends on mcm 5 . A second incision two nucleotides upstream results in the net excision of a di-nucleotide. Expression of phage and plant tRNA repair systems can relieve PaOrf2 toxicity when tRNA cleavage is restricted to the secondary site in elp3 cells that lack the mcm 5 wobble U modification. Whereas the endogenous yeast tRNA ligase Trl1 can heal tRNA halves produced by PaOrf2 cleavage in elp3 cells, its RNA sealing activity is inadequate to complete the repair. Compatible sealing activity can be provided in trans by plant tRNA ligase. The damage-rescuing ability of tRNA repair systems is lost when PaOrf2 can break tRNA at both sites. These results highlight the logic of a two-incision mechanism of tRNA anticodon damage that evades productive repair by tRNA ligases.